The Analysis Study of Diagnostic Imaging Performance and Accuracy of Congestive Heart Failure: A Comprehensive Systematic Review - Mutiara Nurul Mahabbah; Rendi Rafsanjani; Bintara Ayu Putri (International Medical Journal Corp. Ltd, 2025)
Background: Congestive heart failure (CHF) diagnosis requires accurate imaging techniques like echocardiography, magnetic resonance imaging (MRI), and computed tomography (CT). However, challenges persist in diagnostic accuracy due to factors like operator dependency and radiation exposure. This review aims to systematically evaluate the performance and accuracy of various diagnostic imaging modalities in the context of CHF. Methods: This systematic review adhered to PRISMA 2020 guidelines, focusing exclusively on full-text articles published in English between 2014 and 2024. Editorials and review articles without a DOI were excluded to ensure the utilization of high-quality sources. A literature review was conducted utilizing reputable databases including ScienceDirect, PubMed, and SagePub to identify relevant studies. Result: The initial database search identified over 1,000 relevant publications. Through a rigorous three-stage screening process, eight studies met the predefined inclusion criteria for in-depth analysis. Each study underwent a comprehensive critical evaluation, ensuring a high-quality evidence base for assessing the diagnostic imaging performance and accuracy in congestive heart failure. This systematic approach strengthened the study’s relevance, providing meaningful insights into the strengths and limitations of various imaging modalities. Conclusion: Echocardiography, cardiac CT, and cardiac MRI are essential imaging modalities for diagnosing and managing CHF. Echocardiography offers real-time imaging, while cardiac CT provides high-resolution insights. MRI, the gold standard for myocardial tissue characterization, offers unparalleled prognostic value. Integrating these technologies enhances patient outcomes.